Sistem Informasi Geografis Daerah Irigasi di Provinsi Gorontalo Berbasis Web - Djafar, Dzikriansah; Takdir, Rahman; Ahaliki, Budiyanto (Gorontalo State University, 2025)
Abstract Irrigation areas are water supply areas designed to regulate the distribution and use of water efficiently to support activities in the agricultural sector. Management of irrigation areas cannot be separated from the existence of an irrigation information system as regulated in government regulations. This research raises the problem of limited accessibility of information regarding irrigation areas in Gorontalo Province, this is important for monitoring agricultural conditions. This research aims to increase the accessibility of information about irrigation areas through the use of a website-based Geographic Information System, with a focus on mapping the components of irrigation areas using LineString, Polygon and Coordinates and being able to carry out spatial analysis. The RAD (Rapid Application Development) method is used in GIS developments, with fast iteration to build the system. The result of this research is a Geographic Information System for the Irrigation Areas of Gorontalo Province which can facilitate the management and mapping of irrigation area data in Gorontalo Province. Keywords: Information System, Website, Irrigation Area, Gorontalo, Rapid Application Development. Abstrak Daerah irigasi merupakan wilayah pemasok air yang dirancang untuk mengatur distribusi dan penggunaan air secara efisien untuk dapat menunjang aktifitas pada sektor pertanian. Pengelolaan daerah irigasi tidak luput dari adanya sistem informasi irigasi sebagaimana telah diatur dalam peraturan pemerintah. Penelitian ini mengangkat masalah terhadap keterbatasan aksesibilitas Informasi mengenai Daerah irigasi di Provinsi Gorontalo, hal ini penting untuk pemantauan kondisi pertanian. Penelitian ini bertujuan untuk meningkatkan aksesibilitas informasi tentang daerah irigasi melalui pemanfaatan Sistem Informasi Geografis berbasis website, dengan fokus pada pemetaan komponen-komponen pada daerah irigasi dengan menggunakan LineString, Polygon, dan Koordinat serta dapat melakukan analisis spasial. Metode RAD (Rapid Appication Development) digunakan dalam pengembangan-pengembangan GIS, dengan iterasi cepat untuk membangun sistem. Hasil dari penelitian ini yakni sebuah Sistem Informasi Geografis Daerah Irigasi Provinsi Gorontalo yang dapat memudahkan dalam pengelolaan dan pemetaan data daerah irigasi di Provinsi Gorontalo.